Correspondences - Ouzounian, Gascia; Papalexandri–Alexandri, Marianthi (Current Musicology, 2013)
In this series of letters, the musicologist and violinist Gascia Ouzounian (writing from Belfast) and the composer Marianthi Papalexandri–Alexandri (writing from Berlin and Stuttgart) discuss the latter’s music, touching on such topics as: graphic notation; existential therapy; collaboration and communication; “energy” and “live–ness” within musical composition and performance; and site–specific sound installation. Their discussion is supplemented with images, excerpts of scores, and video of Papalexandri–Alexandri’s compositions and installations since 2005.